Upayā-kauśala as the pragmatic justification of Madhyamaka ethical claims - Quist, Andrew, author; MacKenzie, Matthew, advisor; Tucker, Dustin, committee member; Hickey, Matthew, committee member (Colorado State University. Libraries, 2018)
Madhyamaka Buddhism is typically characterized as a particularly thoroughgoing form of anti-foundationalism. This leads to difficulties when trying to justify knowledge claims as well as ethical claims, especially in the light of how these claims are handled in mainstream Abhidharma Buddhism. The ethical domain is particularly important for Buddhism since the Buddhist project is fundamentally soteriological. I endeavor to offer a plausible way that truth claims, especially ethical truth claims, can be justified while keeping to Madhyamaka's metaphysical commitments. Specifically, I will argue that a functional-pragmatist approach – I use the term upāya-kauśalya or "skillful means" – is the most promising way that Madhyamaka can situate the normativity of ethical claims.
Keywords: functional; Madhyamaka; Upāya; justification; ethics; pragmatic